Rational Design of a Water-Storable Hierarchical Architecture Decorated with Amorphous Barium Oxide and Nickel Nanoparticles as a Solid Oxide Fuel Cell Anode with Excellent Sulfur Tolerance - Song, Y.; Wang, Wei; Ge, L.; Xu, X.; Zhang, Z.; Julião, P.; Zhou, W.; Shao, Zongping (WILEY-BLACKWELL, 2017)
© 2017 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim. Solid oxide fuel cells (SOFCs), which can directly convert chemical energy stored in fuels into electric power, represent a useful technology for a more sustainable future. They are particularly attractive given that they can be easily integrated into the currently available fossil fuel infrastructure to realize an ideal clean energy system. However, the widespread use of the SOFC technology is hindered by sulfur poisoning at the anode caused by the sulfur impurities in fossil fuels. Therefore, improving the sulfur tolerance of the anode is critical for developing SOFCs for use with fossil fuels. Herein, a novel, highly active, sulfur-tolerant anode for intermediate-temperature SOFCs is prepared via a facile impregnation and limited reaction protocol. During synthesis, Ni nanoparticles, water-storable BaZr 0.4 Ce 0.4 Y 0.2 O 3- d (BZCY) perovskite, and amorphous BaO are formed in situ and deposited on the surface of a Sm 0.2 Ce 0.8 O 1.9 (SDC) scaffold. More specifically, a porous SDC scaffold is impregnated with a well-designed proton-conducting perovskite oxide liquid precursor with the nominal composition of Ba(Zr 0.4 Ce 0.4 Y 0.2 ) 0.8 Ni 0.2 O 3- d (BZCYN), calcined and reduced in hydrogen. The as-synthesized hierarchical architecture exhibits high H 2 electro-oxidation activity, excellent operational stability, superior sulfur tolerance, and good thermal cyclability. This work demonstrates the potential of combining nanocatalysts and water-storable materials in advanced electrocatalysts for SOFCs.